A century of biological-weapons programs (1915–2015): reviewing the evidence. Issue 1 (2nd January 2017) - Carus, W. Seth
ABSTRACT: This article reviews what is known about the proliferation of biological-weapon programs during the past century. Collecting information on biological-weapon programs is difficult, even for intelligence organizations, and there is limited information available on the extent and character of past programs. A review of the open-source literature supports claims that twenty-three states had, probably had, or possibly had a program. The number of active programs has varied over time, from a low of zero in 1920 to a high of possibly as many as eight in 1990. Program size and sophistication also has varied enormously; most were small and unsophisticated, and many existed for only a short period of time.